Maloklusi pada Remaja Usia 12-17 Tahun di Medan - Lina Natamiharja; U. A. Lubis (Faculty of Dentistry, Universitas Indonesia, 2015)
The aim of this study was to assess the need for orthodontic treatment, prevalence and severity of malocclusion among teenagers. A high school located in a suburban area of Medan was chosen as a cluster sample. All student (213 individuals, males 47,42% and females 52,58%, age 12-17 years) were examined at school. The measurement of malocclusion was performed by one examiner, using Treatment Priority Index (TPI, Grainger, 1967) directly in the mouth. None of the students wore removable of fixed orthodontics alliances. The prevalence need for orthodontic treatment was 59,15%. The prevalence of normal occlusion was 13,62%, mild malocclusion 27,23%, moderate malocclusion 26,76%, severe malocclusion 18,31% and very severe 14,08%. The percentage of disto occlusion was 18,30% and mesio occlusion 0,93% and it was concluded that the prevalence of malocclusion and the need of orthodontic treatment was high, similar as reported in other countries.